LEADERSHIP TRANSFORMATION AT MEKAR ARUM SMA BANDUNG: SYNERGY BETWEEN THE SCHOOL PRINCIPAL AND THE FOUNDATION IN IMPROVING PROFESSIONALISM INFRASTRUCTURE AND TEACHER WELFARE - Basith, Fardan Abdul; Puroman, Eman; As Sidiq, Fazar Rifqi; Badrudin, Badrudin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Leadership in the world of education plays a very vital role in creating a conducive learning environment, improving the quality of teaching, and ensuring the welfare of all parties involved, especially teachers. At Mekar Arum Bandung High School, the leadership transformation carried out by the principal and foundation aims to improve various important aspects, including school infrastructure, teacher professionalism and their welfare. Synergy between school principals and foundations is the main key in realizing this change. Leadership transformation in educational institutions plays a very important role in encouraging the creation of a conducive learning environment and improving the quality of education. Currently, the challenges faced by schools in Indonesia are increasingly complex. One of the main challenges is meeting the need for adequate facilities, both in terms of physical facilities and technology, to support 21st century learning. In addition, demands for teacher professionalism are increasing along with the development of the curriculum and the increasingly diverse needs of students. On the other hand, teacher welfare is often an issue that does not receive serious attention, even though this welfare has a direct impact on their motivation and performance.Mekar Arum Bandung High School is one of the schools that has great potential to develop through close collaboration between the principal as operational leader and the foundation as strategic policy holder. However, this leadership transformation process cannot be free from various obstacles, such as budget limitations, differences in vision between leaders, and the dynamics of the relationship between school principals and foundations. Therefore, good strategy and synergy are needed to ensure that leadership transformation can run effectively.This research aims to examine how the leadership transformation that exists between the principal and the foundation at Mekar Arum Bandung High School can contribute to improving school infrastructure, developing teacher professionalism, and improving the welfare of teaching staff. By understanding the existing dynamics and challenges, it is hoped that the results of this research can provide applicable recommendations to strengthen leadership synergy to achieve quality education goals.